The Protection of Plant Varieties and Farmer’s Rights Act of India: An Analysis - Das, Amruta; Kumar Mohapatra, Chinmaya (International Journal of Psychosocial Rehabilitation, 2025)
In 2001 the Indian Government passed the Protection of Plat Varieties and Farmers’Right Act. After India. After India became a signatory to the Intellectual Property Rights Agreement (TRIPs) on Trade Related Aspects in 1994, a law was required to be formulated. Article 27.3(b) of this agreement requires the member countries to provide for protection of plant varieties either by a patent or by an effective sui generis system or by any combination thereof. The member states therefore had the choice to frame laws that fit their own structure, and India exercised this right. The current Indian Patent Act of 1970 excluded from patentability the production methods of agriculture and horticulture. The sui generis scheme for the defense of plant varieties has been established to incorporate the rights of breeders, farmers and village populations, and to take care of the questions regarding equal profit sharing. Here we are seeking to critically analyze the policy frameworks for their successful implementation